1996
DOI: 10.1038/bjc.1996.434
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in gastric cancer: the value of vascular invasion, mitotic rate and lymphoplasmacytic infiltration

Abstract: Summary A retrospective analysis of 321 gastric cancer patients was made to assess the prognostic value of TNM classification, tumour differentiation, Lauren classification, proliferative rate, inflammatory reaction and tumour invasion in vascular or neural structures of the gastric wall. The TNM classification showed the strongest correlation with survival in univariate and multivariate analyses (P<0.0001). The invasion in lymphatic or vascular system and Lauren classification were also independent prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 25 publications
(28 reference statements)
1
26
1
3
Order By: Relevance
“…While the prognostic significance of poorly differentiated histology in gastric cancer is controversial, several studies have demonstrated that mixed type in Lauren's classification is associated with poor prognosis and other factors suggesting aggressive biologic behavior such as lymph node metastasis and advanced stage (Shiu et al, 1989;Kim et al, 1992;Carneiro et al, 1995;Macdonald et al, 1995;Yu et al, 1995;Setälä et al, 1996;Stelzner and Emmrich, 1997). Unlike the present results, other studies with gastric cancer tissue have failed to show any relationship between TS expression and tumour differentiation or Lauren's classification (Kuniyasu et al, 1998;Yeh et al, 1998;Suda et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…While the prognostic significance of poorly differentiated histology in gastric cancer is controversial, several studies have demonstrated that mixed type in Lauren's classification is associated with poor prognosis and other factors suggesting aggressive biologic behavior such as lymph node metastasis and advanced stage (Shiu et al, 1989;Kim et al, 1992;Carneiro et al, 1995;Macdonald et al, 1995;Yu et al, 1995;Setälä et al, 1996;Stelzner and Emmrich, 1997). Unlike the present results, other studies with gastric cancer tissue have failed to show any relationship between TS expression and tumour differentiation or Lauren's classification (Kuniyasu et al, 1998;Yeh et al, 1998;Suda et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this failure in tumor immunity might be insufficient expression of co-stimulatory or adhesion molecules by tumor cells, or defective processing and presentation of antigens on their cell surface [30][31][32]. Previous studies suggested that gastric carcinoma may require a greater number of TILs to overcome tumor growth than colorectal or esophageal carcinoma [12][13][14][15]. The current study was carried out to elucidate the multiple steps by which gastric carcinoma escapes from immunological defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the number of TILs was found to correlate with survival in colorectal and esophageal carcinoma patients [12,13]. Setälä et al [14] investigated the prognostic value of various clinicopathological factors in 321 gastric carcinoma patients. In their study, the density of lymphocytes and plasma cells was not an independent prognostic predictor on multivariate analysis, despite its power on univariate analysis.…”
Section: Rcas1 (Receptor Binding Cancer Antigen Expressed Onmentioning
confidence: 99%
“…The activity of IL-2 on peritumoral lymphocytes and eosinophils is perhaps not unexpected and may result from direct action on the IL-2 receptor, which is expressed by both activated lymphocytes and eosinophils [168], and an indirect action due to an IL-2-mediated cascade of cytokines and chemokines that results in lymphocyte and eosinophil migration and proliferation. The presence of peritumoral infiltrating lymphocyte is a well described phenomenon in cancer patients and typically relates to a better prognosis as reported in patients with primary malignancies of the lung [169], liver [170], ovary [171], colon [172,173], genitourinary tract [174] and stomach [175]. IL-2 seems not to modify the composition of lymphocytic infiltration, which resulted to be mostly made by T cells, widespread diffused into the tumor, and by B cells, peripherally organized in a nodular shape.…”
Section: Discussionmentioning
confidence: 99%